Field Performance Assessment of Irradiated Aedes albopictus Males Through Mark–Release–Recapture Trials With Multiple Release Points - Balestrino, Fabrizio; Puggioli, Arianna; Malfacini, Marco; Albieri, Alessandro; Carrieri, Marco; Bouyer, Jeremy; Bellini, Romeo (Frontiers in Bioengineering and Biotechnology, 2022)
Mark-release-recapture (MRR) trials have been conducted in Northern Italy to evaluate the capacity of radio-substerilized Aedes albopictus males to survive, disperse and engage in mating in the field. Two MRR sessions with human landing collection method (HLC) were conducted with the simultaneous release of irradiated males marked with four different pigments colours. The survival and dispersal rates seem to be influenced more by environmental factors such as barriers, shading and vegetation rather than weather parameters. In this study we confirmed a positive linear relationship between the sterile adult male’s daily survival rate and the relative humidity previously reported in similar experimental conditions and a different dispersal capacity of the released Ae. albopictus males in low (NDVI index < 0.4) and high (NDVI index > 0.4) vegetated areas. Consistent with previous studies, Ae. albopictus males have their maximal dispersion in the first days after release, while in the following days the males become more stationary. The similar field performances obtained with marked and unmarked radio-sterilised and untreated Ae. albopictus males on similar environment confirm the negligible effects of irradiation and marking procedures on the quality of the males released. The similar sterile to wild (S/W) male ratio measured in high and low vegetation areas in the release sites indicates a similar distribution pattern for the wild and the released sterile males. According to the MRR data collected, the Lincoln index estimated different Ae. albopictus mean population density in the study areas equal to 7,000 and 3,000 male/ha, respectively.